A machine learning-based approach to ERα bioactivity and drug ADMET prediction - An, Tianbo; Chen, Yueren; Chen, Yefeng; Ma, Leyu; Wang, Jingrui; Zhao, Jian (Frontiers in Genetics, 2023)
By predicting ERα bioactivity and mining the potential relationship between ADMET attributes in drug research and development, the development efficiency of specific drugs for breast cancer will be effectively improved and the misjudgment rate of R & D personnel will be reduced. The quantitative prediction model of ERα bioactivity and classification prediction model of ADMET properties were constructed. The prediction results of ERα bioactivity were compared by XGBoot, Light GBM, Random Forest and MLP neural network. Two models with high prediction accuracy were selected and fused to obtain ERα bioactivity prediction model from MAE, MSE and R2. The data were further subjected to model-based feature selection and FDR/FPR-based feature selection, respectively, and the results were placed in a voting machine to obtain ADMET classification prediction model. In this study, 430 molecular descriptors were removed, and finally 20 molecular descriptors with the most significant effect on biological activity obtained by the dual feature screening combined optimization method were used to establish a compound molecular descriptor prediction model for ERα biological activity, and further classification and prediction of the ADMET properties of the drugs were made. Eighty variables were selected by the model ExtraTreesClassifier Classifie, and 40 variables were selected by the model GradientBoostingClassifier to complete the model-based feature selection. At the same time, the feature selection method based on FDR/FPR is also selected, and the three classification models obtained by the two methods are placed into the voting machine to obtain the final model. The experimental results showed that the model 's evaluation indexes and roc diagram were excellent and could accurately predict ERα bioactivity and ADMET properties. The model constructed in this study has high accuracy, fast convergence and robustness, has a very high accuracy for ADMET and ERα classification prediction, has bright prospects in the biopharmaceutical field, and is an important method for energy conservation and yield increase in the future.